Metaplastic Ossification in a Juvenile Rectal Polyp: A Rare Histological Finding - Monika Garg (Journal of Clinical and Diagnostic Research, 2013)
An osseous metaplasia is a phenomenon which has been described in a wide variety of tissue types with respect to both neoplastic and non-neoplastic conditions. However, an osseous metaplasia is exceedingly rare in colonic polyps. We are herein representing a case of osseous metaplasia in a juvenile rectal polyp in a six year old boy, with review of the literature on the suggested mechanisms of its aetiology.